Leksikon Kuliner Khas Madura Sebagai Wujud Pengenalan Kuliner Nusantara [Perspektif Ekolinguistik] - Kamilia, Nabilatul; Khotimah, Khusnul; Ayuningtias, Diah Ikawati (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2024)
This research was conducted to describe 1) typical Madurese food or culinary delights from various districts in Madura and 2) the relationship between the lexicon (naming) of typical Madurese culinary delights when viewed from an ecolinguistic perspective. The theory used as a basic reference in this research is the ecolinguistic theory put forward by Lindo and Bundsgaard. The object of this research is the meaning of naming typical Madurese culinary delights and their relationship to the environment, culture, history, traditions or Madurese language. Meanwhile, typical Madurese culinary delights were used as a data source in this research. The data in this research was taken using reading techniques and note-taking techniques using the document review method. The data collection instrument in this research was the researcher himself (human instrument). The results of this research found 6 typical Madurese culinary data that were influenced by the biological dimension, 2 typical Madurese culinary data that were influenced by the ideological dimension, and 7 typical Madurese culinary data that were influenced by the sociological dimension. The results of the analysis in this research can provide an in-depth understanding of the lexicon (naming) of typical Madurese culinary foods based on an ecolinguistic perspective. It is hoped that this research can be used as a reference for future researchers.Keywords: ecolinguistics, lexicon, Madurese culinary